Revolutionizing Arabic Language Learning: The Transformation of Artificial Intelligence (AI)-Based and Multimedia Cognitive Methods - Teuku Muhammad Fauzan Robbani (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
The rapid development of information technology in the Society 5.0 era requires Arabic language education to move beyond conventional, one-size-fits-all instruction. This study analyzes the effectiveness, prospects, and challenges of integrating Artificial Intelligence (AI) with the Cognitive Theory of Multimedia Learning in Arabic language education. A qualitative, PRISMA-informed systematic literature review and thematic meta-synthesis were conducted using ten core studies, supported by additional theoretical and contextual references. The synthesis shows that generative AI, chatbots, automatic speech recognition, Android-based applications, augmented reality, and Lectora Inspire multimedia can support vocabulary (mufradat), grammar (nahwu and sharaf), speaking, reading, and listening skills by enabling feedback, practice, visualization, and flexible access. However, the evidence is heterogeneous and includes development and qualitative studies; AI-generated Arabic materials may also contain linguistic, dialectal, and transcription errors. The study concludes that these technologies are most effective when cognitive-load principles, teacher mediation, infrastructure readiness, digital literacy, and human verification are integrated into their design and use. The findings imply that AI should function as a pedagogical support system rather than a substitute for educators, and that future research should prioritize controlled, longitudinal, and transparently reported evaluations.